Gambaran Pengetahuan dan Sikap Ibu Hamil Tentang Prenatal Yoga di Puskesmas Putri Ayu Kota Jambi - Sri Maharani (Universitas Baiturrahim, 2020)
ABSTRACTAnxiety and fear experienced by the mother, especially primipara, can prolong the duration of labor and increase the incidence of labor by action, namely labor with cesarean section. Mental health including pregnancy anxiety has been proven to be reduced or eliminated through physical exercise. One of the recommended physical exercises is yoga because it is easy to do and is very beneficial for physical fitness and psychology. Yoga in pregnancy is more effective in reducing anxiety and depression. This study aims to describe the knowledge and attitudes of pregnant women about prenatal yoga. Quantitative research design. The subjects in this study were pregnant women trimester I, II and III in the working area of the Putri Ayu Public Health Center in Jambi. Research subjects were given questionnaires to measure the knowledge and attitudes of pregnant women regarding Prenatal Gentle Yoga. The study was conducted in the working area of the Putri Ayu Public Health Center in Jambi. The data collected was analyzed univariately. The results of the study revealed that 32 mothers who took classes in pregnant women in the working area of Putri Ayu Health Center had less knowledge about prenatal gentle yoga, namely 18 mothers (56.2%) and had a positive attitude of 25 mothers (78%). It is recommended for health workers to provide information about some of the development activities that pregnant women can do to provide comfort during pregnancy, for example with prenatal gentle yoga.